2014
DOI: 10.1590/s1516-35982014000200008
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and visual identification devices for adult goats reared in semi-intensive system

Abstract: -This study intended to evaluate three identification devices for adult goats reared in semi-intensive system. They were (1) the ruminal bolus, electronic identification device composed of non-toxic ceramic and weighing 74.4 g; (2) small ear tag on left ear, visual identification device with dimensions of 50 × 15mm; and (3) big ear tag on right ear, also a visual identification device with dimensions of 42 × 48 mm. Twenty-two crossbred Boer female goats with mean age of 4 years and mean body weight (BW) of 52.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Carne et al (2009b) reported 3.3% infection and 6.5% tissue reaction rates for e-ET in goat kids. On the other hand, Kowalski et al (2014) observed only bleeding in one goat during application of the big visual ear tag. It is thought that the problems in ears with e-ET may be caused by the greater weight due to the presence of a transponder.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Carne et al (2009b) reported 3.3% infection and 6.5% tissue reaction rates for e-ET in goat kids. On the other hand, Kowalski et al (2014) observed only bleeding in one goat during application of the big visual ear tag. It is thought that the problems in ears with e-ET may be caused by the greater weight due to the presence of a transponder.…”
Section: Resultsmentioning
confidence: 92%
“…Mean values of readability in e-ETs and v-ETs has shown remarkable variability, ranging from 92.3% to 100% in e-ETs (Carne et al, 2009b;Carne et al, 2010) and 82.9% to 100% in v-ETs (Carne et al, 2009a, b;Carne et al, 2010;Carne et al, 2011;Kowalski et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Carne et al (2009) reported three (3.3 %) cases of extreme bleeding in 92 electronic ear tag applications. On the other hand, Kowalski et al (2014) observed bleeding in one goat only when using large-type plastic ear tags. The tagging site on the animal's ear as well as ear tag type is significantly associated with the retention of ear tags and the severity of ear lesions.…”
Section: Discussionmentioning
confidence: 87%